MAKING THE CASE FOR TEACHING CHARACTER CHANGE IN COMPLEX TV: THE CLOSER AND MAJOR CRIMES - Hoffman, Emily C. (Dialogue, 6(1), 2019)
Jason Mittel’s 2015 book Complex TV: The Poetics of Contemporary Television Storytelling offers enough material to sustain a semester-long undergraduate course. Because of its approachability and students’ interest in discussing characters, his chapter devoted to viewers’ parasocial relationships and characters’ potential for change is among the most teachable. However, teaching complex television that relies on intensely serialized story elements can make choosing televisual texts for study and discussion challenging. Therefore, series that skew episodic yet still incorporate serial elements, like police procedurals, can prove to be a practical alternative for classroom study. This article describes how using the interrelated police procedurals The Closer and Major Crimes, offers a rare opportunity to analyze long-term, meaningful character growth through the character of Captain Sharon Raydor. Key scenes across the two series demonstrate the unusual process of transforming Sharon Raydor from a one-dimensional antagonist on The Closer to a dynamic protagonist on Major Crimes. This transformation directly engages students with foundational terminology from Mittell’s chapter, such as alignment, access, attachment, and allegiance. Moreover, it allows them to weigh the evolution of Sharon Raydor against the four types of character change Mittell describes. The article shows how this can be effectively accomplished by viewing one full episode from each series plus an isolated scene from an intervening episode of The Closer. Key Words: Complex TV, The Closer, Major Crimes, characters, change, parasocial relationships, police procedurals, gender
Keywords: Type of access: Open Access